Inhibitory Effects of 658 nm Laser Irradiation on Skin Temperature in Anesthetized Rats: Preliminary Results from a Controlled Study. (7th April 2014) - Litscher, Daniela; Wang, Xiaoyu; Schneider, Miriam; Friemel, Chris M.; Litscher, Gerhard
Abstract : Red laser light stimulation can have many physiological effects. The goal of this animal experimental study was to investigate how red laser stimulation influences the temperature of anesthetized rats at different acupuncture points and nonacupoints. For that reason 12 adult male Wistar Han rats (300–380 g) were investigated. Six anesthetized rats underwent red laser stimulation (wavelength 658 nm, output power 40 mW, diameter 500 µm, and duration 10 min) at the Baihui (GV20) acupoint, the Zusanli acupoint (ST36, bilateral), and a control point on the forelimb. The other six rats underwent the same procedure; however, the laser remained switched off. Significant decreases in temperature were found at the acupoints Baihui, Zusanli left, and Zusanli right. In addition there was no significant temperature effect at a control point. During placebo laser irradiation (deactivated laser) there were also significant temperature changes. The mechanism underlying the results is currently unknown, but brain stimulation (via laser or mechanical pressure) and mainly direct central mechanisms may be responsible for the local and peripheral temperature decrease.